2004
DOI: 10.1038/ng1452
|View full text |Cite
|
Sign up to set email alerts
|

RITS acts in cis to promote RNA interference–mediated transcriptional and post-transcriptional silencing

Abstract: RNA interference is a conserved mechanism by which double-stranded RNA is processed into short interfering RNAs (siRNAs) that can trigger both post-transcriptional and transcriptional gene silencing. In fission yeast, the RNA-induced initiation of transcriptional gene silencing (RITS) complex contains Dicer-generated siRNAs and is required for heterochromatic silencing. Here we show that RITS components, including Argonaute protein, bind to all known heterochromatic loci. At the mating-type region, RITS is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
413
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(439 citation statements)
references
References 35 publications
16
413
2
Order By: Relevance
“…The colocalization of PIWI and HP1a in pericentric heterochromatin may indeed reflect a simple relationship between the piRNA pathway, histone modification, and heterochromatin formation similar to the S. pombe system wherein AGO1-mediated TGS locally targets H3K9 methylation to create a binding site for the HP1 homolog Swi6 (Volpe et al 2002;Noma et al 2004). In Drosophila, our data on the specific interaction between PIWI and HP1a raise the possibility of an alternate pathway to HP1a-mediated heterochromatinization: A PIWI-piRNA complex might directly recruit HP1a to piRNA-corresponding genomic sequences, which could then recruit HMTs such as SU(VAR)3-9 to effect nucleation/spreading.…”
Section: Discussionmentioning
confidence: 98%
“…The colocalization of PIWI and HP1a in pericentric heterochromatin may indeed reflect a simple relationship between the piRNA pathway, histone modification, and heterochromatin formation similar to the S. pombe system wherein AGO1-mediated TGS locally targets H3K9 methylation to create a binding site for the HP1 homolog Swi6 (Volpe et al 2002;Noma et al 2004). In Drosophila, our data on the specific interaction between PIWI and HP1a raise the possibility of an alternate pathway to HP1a-mediated heterochromatinization: A PIWI-piRNA complex might directly recruit HP1a to piRNA-corresponding genomic sequences, which could then recruit HMTs such as SU(VAR)3-9 to effect nucleation/spreading.…”
Section: Discussionmentioning
confidence: 98%
“…In fission yeast, RNAirelated targeting of heterochromatin is apparently initiated by bidirectional transcription, leading to the production of dsRNAs that can be diced. Resulting siRNAs are then stably bound to AGO1 within a protein complex known as RITS (RNA-induced initiation of transcriptional gene silencing) (Noma et al 2004;Verdel et al 2004), which also includes a chromodomain protein, Chp1, and a third protein of unknown function (Tas3). The siRNAs are thought to guide the complex to complementary RNA transcripts from a template-engaged DNA-dependent RNA polymerase (Grewal and Moazed 2003;Buhler et al 2006) which appears to be pol II (Djupedal et al 2005;Kato et al 2005).…”
Section: Comparison Of Sirna-dependent Transcriptional Gene Silencingmentioning
confidence: 99%
“…(1,2) miRNAs negatively regulate translation of specific mRNAs by base-pairing with partially or fully complementary sequences in target mRNAs to modulate diverse biological and cellular processes. (3,4) Recent studies have suggested that miRNAs play crucial roles in osteoblast differentiation. (5) miR-133 and miR-135 impeded osteoblast differentiation by inhibiting the runt-related transcription factor 2 (Runx2) and SMAD family member 5 (Smad5) pathways that synergistically contributed to bone formation.…”
mentioning
confidence: 99%